Books. - Killheffer, Robert K.J. (Fantasy & Science Fiction)
Reviews the books `Northern Stars: The Anthology of Canadian Science Fiction,' edited by David G. Hartwell and Glenn Grant and `Alien Shores: An Anthology of Australian Science Fiction,' edited by Peter McNamara and Margaret Winch.